Farmakologija kanabinoidov - Ferjan, Ilonka (Zdravniški vestnik, 2015)
Background: In this article, a facial reconstruction with implant-supported craniofacial epitheses and our clinical experience with the substitution of auricular and orbital region are described. Materials and methods: In this case series, 9 patients with 28 endosseous implants performed in the period between 2006 and 2013 were included. Two-stage and one-stage procedures were opted for; the former in six patients, and the latter in three patients. There were four patients with congenital defects of facial structures, and five patients who had undergone ablative oncological surgery; three among them received postoperative radiotherapy. In two patients adjuvant therapy with hyperbaric oxygen was used before and after implantation. We analysed the success of combined surgical-prosthodontic treatment. Results: We placed 28 titanium implants in 9 patients. A successful osseointegration was observed in 27 implants; only one endosseous implant failed to integrate and fell out of the bone (in an irradiated patient). The final implantsupported epithesis was achieved in six patients. Among them there were five ear-substituting epitheses and one epithesis substituting the eye and periorbital region. The final epithesis could not be made in three patients; in one patient too much keloid formed to fix a prosthodontic bar to the implants, the other two patients died because of the progression of malignancy. Conclusion: The surgical technique for rehabilitation using implant-supported facial epitheses is simple and reliable. In certain indications, it is the only proper option for aesthetic and socially acceptable rehabilitation. The major problem remains soft tissues surrounding the implants. Due to their stability and appearance, the implantsupported epitheses are superior to the adhesiveretained epitheses.
Keywords: cannabis; drug; endocannabinoids; endokanabinoidi; function; funkcija; konoplja; legal status; legalni status; preparations; receptorji; receptors; toksičnost; toxicity; zdravila